THE EFFECT OF BRAND EQUITY ON CONSUMER BUYING BEHAVIOR IN STARBUCKS MANADO TOWN SQUARE - Koapaha, Janet Devina; Tumiwa, Johan (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2016)
Brand equity is an intangible value of brand that may lead to premium pricing. Nowadays, there are so many coffee shops in Manado, whether they are traditional or modern ones. Each coffee shop has their own popularity that makes the competition within the industry even tighter day by day, including Starbucks which is known for having high brand equity. The study aimed to analyze the effect of brand equity on consumer buying behavior in Starbucks Manado Town Square (MTS). This research was done by using quantitative method, and processed using multiple regression analysis. The data were gathered from 100 respondents. The result shows that all the variables of brand equity simultaneously influence the consumer buying behavior in Starbucks Manado Town Square. Brand awareness, perceived quality, and brand loyalty have significant and positive influence on consumer buying behavior in Starbucks Manado Town Square, whereas brand association has no significant and positive influence on consumer buying behavior in Starbucks Manado Town Square. For the company management, it is recommended to improve brand equity so it can be the first choice of coffee shop in consumersâ€™ mind. Â  Keywords: brand equity, brand awareness, consumer buying behavior